Formulation and Acceptability of CelGar Jelly: A Functional Jelly Candy Derived from Garlic and Celery - Maratis, Jerry; Syarifah, Syarifah; Huzaen, Saphira Aurelia; Hidayat, Latricia Aina; Nazreen, Amanda Farren; Indah Wardani, Laila Meiliyandrie; Hidayat, Andri Krisna; Pamungkas, Rian Adi; Wijayanthie, Nadiyah (Jurnal Penelitian Farmasi Dan Herbal, 2026)
Hypertension is a major global health concern due to its often asymptomatic progression and its association with serious complications such as stroke, heart failure, and kidney disease. This study aimed to develop a functional food product, CelGar jelly, formulated from celery (Apium graveolens L.) and garlic (Allium sativum L.), which are traditionally recognized for their potential antihypertensive properties. Three types of tests were conducted to evaluate the product. A hedonic (sensory) test involving 20 untrained panelists assessed consumer acceptance based on color, aroma, taste, and texture using a five-point hedonic scale. Laboratory analysis was performed to determine the moisture and ash content to ensure compliance with food quality standards. In addition, a functional test using a quasi-experimental one-group pretest–posttest design involved 12 respondents with hypertension to evaluate changes in blood pressure before and after the intervention. The results showed that CelGar jelly was generally acceptable to panelists, and the laboratory analysis confirmed that its moisture and ash content met the Indonesian National Standard for jelly candy. The functional test indicated a statistically significant reduction in systolic blood pressure, while no significant change was observed in diastolic blood pressure. These findings suggest that CelGar jelly has potential as a functional food product supporting blood pressure management, although further studies with larger samples are needed to confirm its health benefits